A coal-based hard carbon negative electrode material for sodium electricity and a preparation method thereof and a sodium ion battery
By preparing for the coal -based hard charcoal negative material for sodium ions, the cross -linked effect of carboxylic acid and coal is used to form a hard charcoal "card house" configuration, which solves the lack of sodium ion battery fast charging capacity and insufficient capacity. The problem realizes efficient sodium ion migration and excellent battery performance.
Patent Information
- Application Number
- CN202410467589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-04-18
AI Technical Summary
In the prior art, when developing coal-based hard carbon anode materials for sodium ion batteries, it is difficult to form a rapid migration channel of sodium ions, resulting in insufficient fast charging capacity and capacity of sodium ion batteries, which cannot meet the needs of the power vehicle field.
By mixing raw materials coal and carboxylic acid salt, and in the process of pre -carbonization, with the activation of carboxylic acid salt and the synergistic role of coal associative, the structure of thick -ring aromatics in the coal is accurately regulated to form a hard charcoal "card house" structure. Type, increase the pores of different structures and suitable carbon layers, and promote the rapid migration of sodium ions.
The excellent fast charging ability and high capacity of sodium ion batteries are realized, and the demand for sodium ion batteries in the power vehicle field is simple, safe, safe and reliable, and easy to enlarge.
Smart Images

Figure CN118183741B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a coal-based hard carbon negative electrode material for sodium electricity, a preparation method thereof, and a sodium ion battery. Background Art
[0002] Coal has always been the main energy source and important industrial raw material in my country, and is the ballast of national energy security. The material utilization of coal resources is directly related to the country's economic lifeline and energy security, and is an important part of the country's "big energy strategy". At present, the global energy green and low-carbon transformation means that the energy system is changing from fuel-intensive to material-intensive, so it is particularly necessary to develop green and high-value coal. Coal is a natural material with a complex three-dimensional cross-linked network structure formed by a polycyclic aromatic hydrocarbon molecular structure as a skeleton and an alkyl chain structure as a filler. The unique molecular structure gives it a natural "high reactivity" property. There is great potential in the development of coal-based carbon materials using coal as raw material, especially in the field of coal-based hard carbon negative electrode materials for sodium power.
[0003] Nowadays, coal-based hard carbon negative electrode materials developed with coal as raw material are mostly concentrated in direct carbonization, hydrothermal oxidation and co-carbonization. For example, CN113381013A discloses a coal-based hard carbon negative electrode material for sodium ion batteries and its preparation method and application. The method first deashes the raw coal to obtain a carbon precursor, and then places the carbon precursor in an inert atmosphere for high-temperature carbonization, and obtains the coal-based hard carbon material after programmed cooling. This method regulates the structure of hard carbon through its own N / O / S and other foreign elements, which only changes the crystallites, disorder, and defect structure of the hard carbon, and cannot form a channel for the rapid migration of sodium ions, and the improvement of the fast charging ability of sodium ions is relatively weak. CN111293309A discloses a performance improvement method and application of coal-based sodium ion battery negative electrode materials. The method heat treats a mixture of powdered coke and coal coke powder to obtain a hard carbon material. This method coats the surface of coal-based hard carbon with a soft carbon precursor to improve processing performance and electrochemical properties. The soft carbon precursor affects the surface structural stability of the hard carbon, but does not affect the internal structure of the hard carbon, so its improvement in double charge is limited. CN116553521A discloses mixing a coal-based raw material with an alkaline solution and performing hydrothermal preoxidation to obtain a preoxidized coal-based raw material. The coal-based hard carbon obtained by this method has a large carbon layer structure inside, which is suitable for lithium-ion hard carbon, but is relatively lacking in terms of fast charging and gram capacity of sodium-ion batteries; and, using an alkaline solution to hydrothermally oxidize coal ignores the risk of flammable molecular structures of polycyclic aromatic hydrocarbons in coal.
[0004] In summary, there is an urgent need to develop a low-cost, safe, and high-rate coal-based hard carbon sodium negative electrode material to meet the current demand for sodium-ion batteries in the field of power vehicles. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a coal-based hard carbon negative electrode material for sodium electricity and a preparation method thereof and a sodium ion battery. The present invention provides a low-cost, safe and reliable preparation method, which avoids the path of direct carbonization of coal to form soft carbon, but relies on the synergistic effect of carboxylate activation and coal cross-linking to accurately control the structure of the condensed aromatic hydrocarbon molecules inside the coal, thereby forming a hard carbon "house of cards" configuration, so that the coal-based hard carbon has pores with different structures and suitable carbon layer spacing inside, effectively accelerating the rapid migration speed of sodium ions in the coal-based hard carbon, showing excellent sodium ion battery fast charging capability, and meeting the current demand for sodium ion batteries in the field of power vehicles.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a coal-based hard carbon negative electrode material for sodium power generation, the preparation method comprising the following steps:
[0008] (1) blending raw coal and carboxylate to obtain a mixture, and then pre-carbonizing the mixture to obtain a pre-carbonized material;
[0009] (2) The pre-carbonized material is subjected to high-temperature carbonization and graded to obtain the coal-based hard carbon negative electrode material for sodium power generation.
[0010] The present invention provides a low-cost, safe and reliable preparation method, which avoids the path of direct carbonization of coal to form soft carbon. Instead, in the process of pre-carbonization, the structure of the condensed aromatic hydrocarbon molecules inside the coal is accurately regulated by the synergistic effect of carboxylate activation and coal cross-linking, thereby forming a hard carbon "house of cards" configuration, so that the coal-based hard carbon has pores with different structures and suitable D002 carbon layer spacing, effectively accelerating the rapid migration speed of sodium ions in the coal-based hard carbon, showing excellent sodium ion battery fast charging capability, and meeting the current demand for sodium ion batteries in the field of power vehicles.
[0011] The preparation method provided by the present invention has a simple process, is easy to be industrially scaled up, and avoids the safety problem of dust oxidation and explosion. In addition, no by-products are generated during the entire process of the method, which greatly improves the yield of hard carbon.
[0012] As a preferred technical solution of the present invention, before the raw coal and the carboxylate are blended in step (1), the raw coal and the carboxylate are first crushed.
[0013] It should be noted that the present invention does not limit the method of crushing treatment, and illustratively, it may be a pulverizing treatment.
[0014] Preferably, the particle size D50 of the raw coal in step (1) is 5-50 μm, for example, it can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc., preferably 5-10 μm.
[0015] Preferably, the particle size D50 of the carboxylate in step (1) is 5-100 μm, for example, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, etc., preferably 5-20 μm.
[0016] As a preferred technical solution of the present invention, the raw coal in step (1) includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two of them.
[0017] Preferably, the carboxylate in step (1) comprises any one of citrate, alginate, carbonate, acetate or acetate, or a combination of at least two thereof.
[0018] Preferably, the cations in the carboxylate in step (1) include potassium ions and / or sodium ions.
[0019] Preferably, the citrate includes any one of sodium citrate, potassium citrate or zinc citrate, or a combination of at least two of them.
[0020] Preferably, the alginate comprises potassium alginate and / or sodium alginate.
[0021] Preferably, the carbonate comprises potassium carbonate and / or sodium carbonate.
[0022] Preferably, the acetate comprises sodium acetate and / or potassium acetate.
[0023] Preferably, the acetate comprises sodium acetate and / or potassium acetate.
[0024] Preferably, the mass ratio of the raw coal and the carboxylate in step (1) is (2-20):1, for example, it can be 2:1, 5:1, 10:1, 15:1 or 20:1, etc.
[0025] In the present invention, if the mass ratio of raw coal and carboxylate is too large, that is, the amount of carboxylate used is too small, the cross-linking effect on the raw coal is small, and the pores inside the raw coal are mostly semi-open pores, the capacity of the hard carbon negative electrode material is low, and the rate performance is poor; if the mass ratio of carboxylate and raw coal is too small, that is, the amount of carboxylate used is too much, the activation and pore-forming effect on the raw coal is obvious, so that more pores and a high specific surface area are formed inside, resulting in a decrease in the first effect of the hard carbon negative electrode material and a deterioration in the capacity performance.
[0026] As a preferred technical solution of the present invention, the blending process in step (1) is accompanied by stirring, and the stirring rate is 20-1000rpm, for example, it can be 20rpm, 50rpm, 100rpm, 300rpm, 500rpm, 700rpm or 900rpm.
[0027] Preferably, the blending time in step (1) is 0.5-5 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h.
[0028] As a preferred technical solution of the present invention, the pre-carbonization treatment in step (1) is carried out in an inert atmosphere.
[0029] It should be noted that the present invention does not limit the gas in the inert atmosphere, and illustratively, it may be argon or nitrogen.
[0030] Preferably, the temperature of the pre-carbonization treatment in step (1) is 600-850°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C or 850°C, and the time of the pre-carbonization treatment is 1-5h, for example, 1h, 2h, 3h, 4h or 5h.
[0031] In the present invention, if the temperature of the pre-carbonization treatment is too low, almost no cross-linking and activation will occur between the carboxylate and the raw coal; if the temperature of the pre-carbonization treatment is too high, the activation and pore-forming effect of the carboxylate on the raw coal will be intense, the cross-linking effect will be low, and a large amount of carbon will escape in the form of gas, resulting in a low carbon yield.
[0032] Preferably, the heating rate of the pre-carbonization treatment in step (1) is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.
[0033] As a preferred technical solution of the present invention, before the pre-carbonized material is subjected to high-temperature carbonization in step (2), the pre-carbonized material is pre-treated, and the pre-treatment steps include water washing and drying.
[0034] In the present invention, the purpose of washing with water is to remove components soluble in water.
[0035] Preferably, during the water washing process, the weight ratio of water to the pre-carbonized material is (5-10):1, for example, it can be 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1.
[0036] Preferably, the water washing temperature is 40-80°C, for example, 40°C, 50°C, 60°C, 70°C or 80°C, and the water washing time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h or 3h.
[0037] Preferably, the drying temperature is 100-120°C, for example, 100°C, 105°C, 110°C, 115°C or 120°C, and the drying time is 4-10h, for example, 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0038] As a preferred technical solution of the present invention, the high-temperature carbonization process in step (2) is carried out in an inert atmosphere.
[0039] It should be noted that the present invention does not limit the gas in the inert atmosphere, and illustratively, it may be argon or nitrogen.
[0040] Preferably, the temperature of the high-temperature carbonization in step (2) is 1100-1600°C, for example, it can be 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, and the time of high-temperature carbonization is 1-10h, for example, it can be 1h, 3h, 5h, 7h or 9h, etc.
[0041] In the present invention, if the temperature of high-temperature carbonization is too low, the abundant pores generated in the pre-carbonization stage cannot be closed, so that the surface area of the formed hard carbon is too large, resulting in a low initial coulombic efficiency of the hard carbon negative electrode material; if the temperature of high-temperature carbonization is too high, the interlayer spacing of the hard carbon formed by the raw coal is low, which is not suitable for the migration of sodium ions between carbon layers and the stability of the interlayer compounds is poor, resulting in a low capacity of the hard carbon negative electrode material.
[0042] Preferably, the heating rate of the high temperature carbonization in step (2) is 1-10°C / min, for example, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc.
[0043] Preferably, the classification process in step (2) is carried out in an air flow classifier, and the specific process parameters include:
[0044] The frequency of the induced draft fan is 40-50 Hz, for example, it can be 40 Hz, 42 Hz, 44 Hz, 46 Hz, 48 Hz or 50 Hz, etc. The frequency of the classifying wheel is 50-80 Hz, for example, it can be 50 Hz, 60 Hz, 70 Hz or 80 Hz, etc.
[0045] The purpose of the classification treatment in the present invention is to remove particles with a particle size D50≤0.5 μm, and the remaining material is the coal-based hard carbon negative electrode material.
[0046] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0047] (I) Under stirring conditions, the crushed raw coal and the carboxylate are blended at a mass ratio of (2-20):1 for 0.5-5 hours to obtain a mixture;
[0048] The particle size D50 of the raw coal is 5-50 μm, the particle size D50 of the carboxylate is 5-100 μm, and the stirring rate is 20-1000 rpm;
[0049] (II) in an inert atmosphere, heating the mixture to 600-850° C. at a heating rate of 1-10° C. / min, and pre-carbonizing the mixture for 1-5 hours to obtain a pre-carbonized material;
[0050] (III) washing the pre-carbonized material with water at 40-80° C. for 1-3 hours, and then drying it at 100-120° C. for 4-10 hours;
[0051] Wherein, the weight ratio of water to pre-carbonized material during the water washing process is (5-10):1;
[0052] (IV) In an inert atmosphere, the temperature is raised to 1100-1600°C at a heating rate of 1-10°C / min, and the pre-carbonized material treated in step (III) is subjected to high-temperature carbonization for 1-10h, followed by classification in an air classifier to remove particles with a particle size D50≤0.5μm, with the induced draft fan frequency of 40-50Hz and the classifying wheel frequency of 50-80Hz, to obtain the coal-based hard carbon negative electrode material for sodium power generation.
[0053] In a second aspect, the present invention provides a coal-based hard carbon negative electrode material for sodium power generation, wherein the coal-based hard carbon negative electrode material for sodium power generation is prepared by the preparation method described in the first aspect.
[0054] As a preferred technical solution of the present invention, the particle size D10 of the coal-based hard carbon negative electrode material for sodium power generation is 1-3μm, for example, it can be 1μm, 2μm or 3μm, etc., the particle size D50 is 4-10μm, for example, it can be 4μm, 5μm, 6μm, 8μm or 10μm, etc., and the particle size D90 is 10-16.5μm, for example, it can be 10μm, 12μm, 14μm, 15μm, 16μm or 16.5μm, etc.
[0055] Preferably, the compaction density of the coal-based hard carbon negative electrode material for sodium power generation is 0.95-1.05 g / cm 3 , for example, it can be 0.95 g / cm3 , 0.97g / cm 3 , 1g / cm 3 , 1.02g / cm 3 or 1.05g / cm 3 etc., the tap density is 0.78-0.86g / cm 3 , for example, it can be 0.78 g / cm 3 , 0.8g / cm 3 , 0.82g / cm 3 、0.84g / cm 3 or 0.86g / cm 3 wait.
[0056] Preferably, the specific surface area of the coal-based hard carbon negative electrode material for sodium power generation is 2-8 cm 2 / g, for example, it can be 2cm 2 / g, 4cm 2 / g, 6cm 2 / g or 8cm 2 / g, etc.
[0057] Preferably, the coal-based hard carbon negative electrode material for sodium power generation has a pore structure inside, and the pore structure includes any one of through pores, semi-open pores or closed pores, or a combination of at least two of them.
[0058] In a third aspect, the present invention provides a sodium ion battery, wherein the negative electrode of the sodium ion battery comprises the coal-based hard carbon negative electrode material for sodium electricity as described in the second aspect.
[0059] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] (1) The present invention provides a low-cost, safe and reliable preparation method, which avoids the path of direct carbonization of coal to form soft carbon. Instead, the method uses the synergistic effect of carboxylate activation and coal cross-linking to accurately control the structure of the polycyclic aromatic hydrocarbon molecules inside the coal, thereby forming a hard carbon "house of cards" configuration, so that the coal-based hard carbon has pores with different structures and suitable carbon layer spacing inside, effectively accelerating the rapid migration speed of sodium ions in the coal-based hard carbon, showing excellent sodium ion battery fast charging capability, and meeting the current demand for sodium ion batteries in the field of power vehicles.
[0062] (2) The preparation method provided by the present invention has a simple process and is easy to scale up industrially, thus avoiding the safety problem of dust oxidation and explosion.
[0063] (3) The coal-based hard carbon negative electrode material for sodium power generation prepared by the preparation method provided by the present invention has a gram capacity of 279.3-289.5 mAh / g, a first efficiency of 90.8-92.5%, and a 5C / 1C capacity retention rate of ≧85%. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a process flow chart for preparing coal-based hard carbon negative electrode material in Example 1 of the present invention.
[0065] Figure 2 Schematic diagram of the pores of the pre-carbonized material in Example 1 of the present invention.
[0066] Figure 3 This is a morphology diagram of the coal-based hard carbon negative electrode material prepared in Example 1 of the present invention.
[0067] Figure 4 This is a particle size distribution diagram of the coal-based hard carbon negative electrode material prepared in Example 1 of the present invention.
[0068] Figure 5 This is a charge and discharge curve diagram of the coal-based hard carbon negative electrode material prepared in Example 2 of the present invention.
[0069] Figure 6 This is a comparison chart of X-ray diffraction of coal-based hard carbon negative electrode materials prepared in Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0071] Example 1
[0072] This embodiment provides a method for preparing a coal-based hard carbon negative electrode material for sodium power generation, and its process flow chart is as follows: Figure 1 As shown, the preparation method comprises the following steps:
[0073] (1) Mechanically grinding the coke to obtain a particle size D50 of 6.5 μm; mechanically grinding the sodium citrate particles to obtain a particle size D50 of 5 μm;
[0074] Under stirring conditions, the crushed coke and sodium citrate particles were blended in a mixer at a mass ratio of 20:1 for 0.5 h at a mixer speed of 1000 rpm to obtain a mixture;
[0075] (2) in a nitrogen atmosphere, heating the mixture to 600° C. at a heating rate of 10° C. / min, performing a pre-carbonization treatment on the mixture for 5 hours, and obtaining a pre-carbonized material after cooling;
[0076] (3) pouring the pre-carbonized material into 60° C. water, washing it for 2 hours, and then drying it at 120° C. for 4 hours;
[0077] Wherein, the weight ratio of water to pre-carbonized material during the water washing process is 10:1;
[0078] (4) In a nitrogen atmosphere, the temperature is raised to 1100° C. at a heating rate of 1° C. / min, and the pre-carbonized material treated in step (3) is subjected to high-temperature carbonization for 10 hours. After the cold zone is completed, a high-temperature carbonized material is obtained. The high-temperature carbonized material is then placed in an air flow classifier for classification to remove particles with a particle size D50 ≤ 0.5 μm. The frequency of the induced draft fan is 50 Hz, and the frequency of the classifying wheel is 50 Hz. After the end, the coal-based hard carbon negative electrode material for sodium power generation is obtained.
[0079] This embodiment also provides a sodium power generation coal-based hard carbon negative electrode material, which is prepared by the above-mentioned preparation method, and the particle size D10 of the sodium power generation coal-based hard carbon negative electrode material is 1.8 μm, the particle size D50 is 6.0 μm, and the particle size D90 is 15.4 μm;
[0080] The compaction density of the coal-based hard carbon negative electrode material for sodium power generation is 0.96 g / cm 3 , tap density is 0.82g / cm 3 , with a specific surface area of 8.9 cm 2 / g.
[0081] Figure 2 The schematic diagram of the pores of the pre-carbonized material in this embodiment is shown. As can be seen from the figure, the pre-carbonized material has a variety of pore structures, including through holes and semi-open holes.
[0082] Figure 3 The morphology of the coal-based hard carbon negative electrode material prepared in this example is shown. It can be seen from the figure that the coal-based hard carbon particles present a typical irregular shape and the particle surface is relatively smooth.
[0083] Figure 4 The particle size distribution diagram of the coal-based hard carbon negative electrode material prepared in this embodiment is shown. It can be seen from the figure that the coal-based hard carbon is composed of particles of different sizes, and the particle size range presents a normal distribution curve.
[0084] Example 2
[0085] This embodiment provides a method for preparing a coal-based hard carbon negative electrode material for sodium power generation, the preparation method comprising the following steps:
[0086] (1) Mechanically grinding long flame coal to obtain a particle size D50 of 5 μm; mechanically grinding potassium alginate particles to obtain a particle size D50 of 10 μm;
[0087] Under stirring conditions, the crushed long flame coal and potassium alginate particles were blended in a mixer at a mass ratio of 5:1 for 2 hours at a mixer speed of 500 rpm to obtain a mixture;
[0088] (2) in a nitrogen atmosphere, heating the mixture to 800° C. at a heating rate of 5° C. / min, performing a pre-carbonization treatment on the mixture for 2 h, and obtaining a pre-carbonized material after cooling;
[0089] (3) pouring the pre-carbonized material into 80° C. water, washing it for 5 hours, and then drying it at 100° C. for 8 hours;
[0090] In the water washing process, the weight ratio of water to pre-carbonized material is 5:1;
[0091] (4) In a nitrogen atmosphere, the temperature is raised to 1300° C. at a heating rate of 2° C. / min, and the pre-carbonized material treated in step (3) is subjected to high-temperature carbonization for 2 hours. After the cold zone is completed, a high-temperature carbonized material is obtained. The high-temperature carbonized material is then placed in an air classifier for classification to remove particles with a particle size D50 ≤ 0.5 μm. The frequency of the induced draft fan is 50 Hz, and the frequency of the classifying wheel is 80 Hz. After the end, the coal-based hard carbon negative electrode material for sodium power generation is obtained.
[0092] This embodiment also provides a sodium power generation coal-based hard carbon negative electrode material, the sodium power generation coal-based hard carbon negative electrode material is prepared by the preparation method described above, the sodium power generation coal-based hard carbon negative electrode material has a particle size D10 of 1.1 μm, a particle size D50 of 4.6 μm, and a particle size D90 of 11.8 μm;
[0093] The compaction density of the coal-based hard carbon negative electrode material for sodium electricity is 0.99 g / cm 3 , tap density is 0.8g / cm 3 , with a specific surface area of 5.4 cm 2 / g.
[0094] Figure 5 The charge and discharge curve of the coal-based hard carbon negative electrode material prepared in this embodiment is shown. It can be seen from the figure that the coal-based hard carbon presents a typical charge and discharge curve. The discharge curve consists of a high-voltage slope segment and a low-voltage platform segment. The first discharge capacity is 310.6 mAh / g, the first charge capacity is 281.9 mAh / g, and the first coulombic efficiency is 90.7%.
[0095] Example 3
[0096] This embodiment provides a method for preparing a coal-based hard carbon negative electrode material for sodium power generation, the preparation method comprising the following steps:
[0097] (1) mechanically grinding lignite to a particle size D50 of 10 μm; mechanically grinding sodium acetate particles to a particle size D50 of 20 μm;
[0098] Under stirring conditions, the crushed lignite and sodium acetate particles were blended in a mixer at a mass ratio of 2:1 for 5 hours at a mixer speed of 20 rpm to obtain a mixture;
[0099] (2) in a nitrogen atmosphere, heating the mixture to 850° C. at a heating rate of 10° C. / min, performing a pre-carbonization treatment on the mixture for 5 hours, and obtaining a pre-carbonized material after cooling;
[0100] (3) pouring the pre-carbonized material into 80° C. water, washing it for 5 hours, and then drying it at 120° C. for 8 hours;
[0101] Wherein, the weight ratio of water to pre-carbonized material during the water washing process is 10:1;
[0102] (4) In a nitrogen atmosphere, the temperature is raised to 1600° C. at a heating rate of 10° C. / min, and the pre-carbonized material treated in step (3) is subjected to high-temperature carbonization for 10 hours. After the cold zone is completed, a high-temperature carbonized material is obtained. The high-temperature carbonized material is then placed in an air flow classifier for classification to remove particles with a particle size D50 ≤ 0.5 μm. The frequency of the induced draft fan is 40 Hz, and the frequency of the classifying wheel is 60 Hz. After the end, the coal-based hard carbon negative electrode material for sodium power generation is obtained.
[0103] This embodiment also provides a sodium power generation coal-based hard carbon negative electrode material, the sodium power generation coal-based hard carbon negative electrode material is prepared by the preparation method described above, the particle size D10 of the sodium power generation coal-based hard carbon negative electrode material is 2.1 μm, the particle size D50 is 8.9 μm, and the particle size D90 is 16.3 μm;
[0104] The compaction density of the coal-based hard carbon negative electrode material for sodium electricity is 1.01 g / cm 3 , tap density is 0.82g / cm 3 , with a specific surface area of 2cm 2 / g.
[0105] Example 4
[0106] This embodiment provides a method for preparing a coal-based hard carbon negative electrode material for sodium power generation, the preparation method comprising the following steps:
[0107] (1) Mechanically grinding the non-sticky coal to obtain a particle size D50 of 8 μm; mechanically grinding the sodium citrate particles to obtain a particle size D50 of 16 μm;
[0108] Under stirring conditions, the crushed non-sticky coal and sodium citrate particles were blended in a mixer at a mass ratio of 10:1 for 3 hours at a mixer speed of 100 rpm to obtain a mixture;
[0109] (2) in a nitrogen atmosphere, heating the mixture to 750° C. at a heating rate of 6° C. / min, performing a pre-carbonization treatment on the mixture for 3 h, and obtaining a pre-carbonized material after cooling;
[0110] (3) pouring the pre-carbonized material into 80° C. water, washing it for 2 hours, and then drying it at 120° C. for 6 hours;
[0111] In the water washing process, the weight ratio of water to pre-carbonized material is 8:1;
[0112] (4) In a nitrogen atmosphere, the temperature is raised to 1400° C. at a heating rate of 5° C. / min, and the pre-carbonized material treated in step (3) is subjected to high-temperature carbonization for 3 hours. After the cold zone is completed, a high-temperature carbonized material is obtained. The high-temperature carbonized material is then placed in an air flow classifier for classification to remove particles with a particle size D50 ≤ 0.5 μm. The frequency of the induced draft fan is 45 Hz, and the frequency of the classifying wheel is 50 Hz. After the end, the coal-based hard carbon negative electrode material for sodium power generation is obtained.
[0113] This embodiment also provides a sodium power generation coal-based hard carbon negative electrode material, the sodium power generation coal-based hard carbon negative electrode material is prepared by the preparation method described above, the particle size D10 of the sodium power generation coal-based hard carbon negative electrode material is 1.9 μm, the particle size D50 is 7.1 μm, and the particle size D90 is 14.7 μm;
[0114] The compaction density of the coal-based hard carbon negative electrode material for sodium electricity is 0.95 g / cm 3 , tap density is 0.86g / cm 3 , with a specific surface area of 4.7 cm 2 / g.
[0115] Example 5
[0116] This embodiment provides a method for preparing a coal-based hard carbon negative electrode material for sodium power generation, the preparation method comprising the following steps:
[0117] (1) mechanically grinding anthracite so that the particle size D50 after grinding is 10 μm; mechanically grinding sodium citrate particles so that the particle size D50 after grinding is 10 μm;
[0118] Under stirring conditions, the crushed anthracite and sodium citrate particles were blended in a mixer at a mass ratio of 3:1 for 5 hours at a mixer speed of 300 rpm to obtain a mixture;
[0119] (2) in a nitrogen atmosphere, heating the mixture to 650° C. at a heating rate of 8° C. / min, performing a pre-carbonization treatment on the mixture for 5 hours, and obtaining a pre-carbonized material after cooling;
[0120] (3) pouring the pre-carbonized material into 70° C. water, washing it for 5 hours, and then drying it at 115° C. for 6 hours;
[0121] In the water washing process, the weight ratio of water to pre-carbonized material is 5:1;
[0122] (4) In a nitrogen atmosphere, the temperature is raised to 1500° C. at a heating rate of 3° C. / min, and the pre-carbonized material treated in step (3) is subjected to high-temperature carbonization for 10 hours. After the cold zone is completed, a high-temperature carbonized material is obtained. The high-temperature carbonized material is then placed in an air classifier for classification to remove particles with a particle size D50 ≤ 0.5 μm. The frequency of the induced draft fan is 40 Hz, and the frequency of the classifying wheel is 70 Hz. After the end, the coal-based hard carbon negative electrode material for sodium power generation is obtained.
[0123] This embodiment also provides a sodium power generation coal-based hard carbon negative electrode material, the sodium power generation coal-based hard carbon negative electrode material is prepared by the preparation method described above, the particle size D10 of the sodium power generation coal-based hard carbon negative electrode material is 1.7 μm, the particle size D50 is 9.2 μm, and the particle size D90 is 15.6 μm;
[0124] The compaction density of the coal-based hard carbon negative electrode material for sodium electricity is 1.05 g / cm 3 , tap density is 0.83g / cm 3 , with a specific surface area of 4.2cm 2 / g.
[0125] Example 6
[0126] The difference between this embodiment and embodiment 1 is that the mass ratio of the crushed coke and the sodium citrate particles in step (1) is 1:1.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Example 7
[0129] The difference between this embodiment and embodiment 1 is that the mass ratio of the crushed coking coal and the sodium citrate particles in step (1) is 25:1.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Example 8
[0132] The difference between this embodiment and embodiment 1 is that the temperature of the pre-carbonization treatment in step (2) is 500°C.
[0133] The rest of the preparation methods and parameters were the same as those in Example 1.
[0134] Example 9
[0135] The difference between this embodiment and embodiment 1 is that the temperature of the pre-carbonization treatment in step (2) is 900°C.
[0136] The rest of the preparation methods and parameters were the same as those in Example 1.
[0137] Example 10
[0138] The difference between this embodiment and embodiment 1 is that the temperature of high temperature carbonization in step (4) is 1000°C.
[0139] The rest of the preparation methods and parameters were the same as those in Example 1.
[0140] Embodiment 11
[0141] The difference between this embodiment and embodiment 1 is that the temperature of high temperature carbonization in step (4) is 1700°C.
[0142] The rest of the preparation methods and parameters were the same as those in Example 1.
[0143] Comparative Example 1
[0144] The difference between this comparative example and Example 1 is that no sodium citrate particles are added in step (1).
[0145] The rest of the preparation methods and parameters were the same as those in Example 1.
[0146] Figure 6 The X-ray diffraction comparison diagram of the coal-based hard carbon negative electrode material prepared in Example 1 and Comparative Example 1 is shown. It can be seen from the figure that the X-ray diffraction curve of the hard carbon material prepared in Example 1 shows the presence of a typical bulge peak, indicating that the interior of the hard carbon is an amorphous structure with a large interlayer spacing, D002 is 0.385nm; while the X-ray diffraction curve of the hard carbon material prepared in Comparative Example 1 shows a relatively sharp peak, indicating that its interior is mostly an ordered carbon layer structure with a small interlayer spacing, D002 is only 0.355nm.
[0147] Comparative Example 2
[0148] The difference between this comparative example and Example 1 is that step (2) is not performed, but the mixed material obtained in step (1) is directly washed, dried and carbonized at high temperature.
[0149] The rest of the preparation methods and parameters were the same as those in Example 1.
[0150] Performance Testing
[0151] The coal-based hard carbon negative electrode material for sodium power generation prepared in the above embodiments and comparative examples is made into a sodium ion battery, and the specific steps include: mixing the prepared coal-based hard carbon negative electrode material for sodium power generation, a conductive agent Super P, carboxymethyl cellulose and styrene-butadiene rubber to form a slurry, wherein the mass ratio of the coal-based hard carbon negative electrode material for sodium power generation, Super P, carboxymethyl cellulose and styrene-butadiene rubber in the slurry is 80:10:2:8, and then scraping the slurry on a copper foil, and then drying it in a vacuum drying oven at 100°C for 12h to obtain a negative electrode plate, wherein the active material loading of the negative electrode plate is greater than 3mg cm -2 The counter electrode of the button half-cell is metallic sodium, the separator is GF / D glass fiber, and the electrolyte is 1M NaClO 4 (The solvents included ethylene carbonate and diethyl carbonate, with a volume ratio of 1:1). All assembly processes were performed in a glove box (H 2 O and O 2 The content of each was <0.1ppm).
[0152] The electrochemical performance test of the sodium ion battery prepared above is carried out, including:
[0153] Charge and discharge test: The voltage range is 0-2V, and the charge and discharge test is carried out at a current density of 30mA / g to obtain the discharge specific capacity and first efficiency.
[0154] Fast charging performance test: voltage range 0-2V, cycle 5 times at current densities of 0.1C, 0.25C, 0.5C, 1C, 2.5C, 5C, and 10C, where 1C = 300mAh / g. Record the ratio of the discharge capacity at 5C to the discharge capacity at 1C, which is the 5C / 1C capacity retention rate.
[0155] The above test results are shown in Table 1.
[0156] Table 1
[0157]
[0158] analyze:
[0159] As can be seen from the above table, the method provided by the present invention avoids the path of direct carbonization of coal to form soft carbon. Instead, in the process of pre-carbonization, with the synergistic effect of carboxylate activation and coal cross-linking, the structure of the polycyclic aromatic hydrocarbon molecules inside the coal is precisely regulated, thereby forming a hard carbon "house of cards" configuration, so that the coal-based hard carbon has pores with different structures and suitable carbon layer spacing inside, which effectively accelerates the rapid migration speed of sodium ions in the coal-based hard carbon, demonstrates excellent sodium ion battery fast charging capability, and meets the current demand for sodium ion batteries in the field of power vehicles.
[0160] It can be seen from Example 1 and Examples 6-7 that if the mass ratio of raw coal and carboxylate is too large, that is, the amount of carboxylate used is too small, the cross-linking effect of carboxylate on the raw coal is small, and the pores inside the raw coal are mostly semi-open pores, resulting in a low gram capacity of the hard carbon negative electrode material and poor rate performance; if the mass ratio of raw coal and carboxylate is too small, that is, the amount of carboxylate used is too much, the carboxylate has a significant activation and pore-forming effect on the raw coal, forming more pores and a high specific surface area inside the raw coal, resulting in a decrease in the first effect of the hard carbon negative electrode material and a deterioration in the capacity performance.
[0161] It can be seen from Example 1 and Examples 8-9 that if the temperature of the pre-carbonization treatment is too low, there is almost no cross-linking and activation between the carboxylate and the raw coal, and the gram capacity, first coulomb efficiency, and rate performance of the coal-based hard carbon are slightly improved; if the temperature of the pre-carbonization treatment is too high, the carboxylate has a severe pore-forming effect on the raw coal, the cross-linking effect is low, and a large amount of carbon escapes in the form of gas, resulting in a low carbon yield, and a weak effect on the gram capacity, first coulomb efficiency, and rate performance.
[0162] It can be seen from Example 1 and Examples 10-11 that if the temperature of high-temperature carbonization is too low, the abundant pores generated in the pre-carbonization stage cannot be closed, so that the surface area of the formed hard carbon is too large, resulting in a low initial coulombic efficiency of the hard carbon negative electrode material; if the temperature of high-temperature carbonization is too high, the interlayer spacing of the hard carbon formed by the raw coal will be low, which is not suitable for the migration of sodium ions between carbon layers and the stability of the interlayer compounds is poor, resulting in a low capacity of the hard carbon negative electrode material.
[0163] It can be seen from Example 1 and Comparative Example 1 that if sodium citrate particles are not added in step (1), the coal is directly subjected to pre-carbonization and high-temperature carbonization treatment. Due to the lack of carboxylate crosslinking and activation process, the hard carbon negative electrode material has a low gram capacity, a low first coulombic efficiency and a poor rate performance.
[0164] It can be seen from Example 1 and Comparative Example 2 that if the pre-carbonization treatment is not performed, the cross-linking activation effect of the carboxylate is weak, resulting in poor gram capacity, first coulombic efficiency and rate performance of the hard carbon negative electrode material.
[0165] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a coal-based hard carbon negative electrode material for sodium power generation, characterized in that: The preparation method comprises the following steps: (1) blending raw coal and carboxylate to obtain a mixture, and then pre-carbonizing the mixture to obtain a pre-carbonized material; (2) subjecting the pre-carbonized material to high-temperature carbonization and obtaining the coal-based hard carbon negative electrode material for sodium power generation after graded treatment; Wherein, the carboxylate in step (1) comprises any one of citrate, alginate, carbonate, acetate or acetate, or a combination of at least two thereof; The mass ratio of the raw coal and the carboxylate in step (1) is (2-20):
1.
2. The preparation method according to claim 1, characterized in that: In step (1), before the raw coal and the carboxylate are blended, the raw coal and the carboxylate are firstly crushed.
3. The preparation method according to claim 1, characterized in that: The particle size D50 of the raw coal in step (1) is 5-50 μm.
4. The preparation method according to claim 1, characterized in that: The particle size D50 of the carboxylate in step (1) is 5-100 μm.
5. The preparation method according to claim 1, characterized in that: The raw coal in step (1) includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two of them.
6. The preparation method according to claim 1, characterized in that: The cations in the carboxylate in step (1) include potassium ions and / or sodium ions.
7. The preparation method according to claim 1, characterized in that: The blending process in step (1) is accompanied by stirring, and the stirring rate is 20-1000 rpm.
8. The preparation method according to claim 1, characterized in that: The blending time is 0.5-5h.
9. The preparation method according to claim 1, characterized in that: The pre-carbonization treatment in step (1) is carried out in an inert atmosphere.
10. The preparation method according to claim 1, characterized in that: The temperature of the pre-carbonization treatment in step (1) is 600-850° C., and the time of the pre-carbonization treatment is 1-5 hours.
11. The preparation method according to claim 1, characterized in that: The heating rate of the pre-carbonization treatment in step (1) is 1-10°C / min.
12. The preparation method according to claim 1, characterized in that: Step (2) Before the pre-carbonized material is subjected to high-temperature carbonization, the pre-carbonized material is pre-treated, and the pre-treatment steps include water washing and drying.
13. The preparation method according to claim 1, characterized in that: The high-temperature carbonization process in step (2) is carried out in an inert atmosphere.
14. The preparation method according to claim 1, characterized in that: The temperature of the high-temperature carbonization in step (2) is 1100-1600° C., and the time of the high-temperature carbonization is 1-10 h.
15. The preparation method according to claim 1, characterized in that: The heating rate of the high temperature carbonization in step (2) is 1-10°C / min.
16. The preparation method according to claim 1, characterized in that: The classification process in step (2) is carried out in an airflow classifier, and the specific process parameters include: The frequency of the induced draft fan is 40-50Hz, and the frequency of the classifying wheel is 50-80Hz.
17. The preparation method according to any one of claims 1 to 16, characterized in that: The preparation method comprises the following steps: (I) Under stirring conditions, the crushed raw coal and the carboxylate are blended at a mass ratio of (2-20):1 for 0.5-5 hours to obtain a mixture; The particle size D50 of the raw coal is 5-50 μm, the particle size D50 of the carboxylate is 5-100 μm, and the stirring rate is 20-1000 rpm; (II) in an inert atmosphere, heating the mixture to 600-850° C. at a heating rate of 1-10° C. / min, and pre-carbonizing the mixture for 1-5 hours to obtain a pre-carbonized material; (III) washing the pre-carbonized material with water at 40-80° C. for 1-3 hours, and then drying it at 100-120° C. for 4-10 hours; Wherein, the weight ratio of water to pre-carbonized material during the water washing process is (5-10):1; (IV) In an inert atmosphere, the temperature is raised to 1100-1600°C at a heating rate of 1-10°C / min, and the pre-carbonized material treated in step (III) is subjected to high-temperature carbonization for 1-10h, followed by classification in an air classifier to remove particles with a particle size D50≤0.5μm, with the induced draft fan frequency of 40-50Hz and the classifying wheel frequency of 50-80Hz, to obtain the coal-based hard carbon negative electrode material for sodium power generation.
18. A coal-based hard carbon negative electrode material for sodium power generation, characterized in that: The coal-based hard carbon negative electrode material for sodium power generation is prepared by the preparation method described in any one of claims 1 to 17.
19. A sodium ion battery, characterized in that: The negative electrode of the sodium ion battery includes the coal-based hard carbon negative electrode material for sodium electricity as described in claim 18.
Citation Information
Patent Citations
Performance improvement method of coal-based sodium ion battery negative electrode material and application thereof
CN111293309A
Coal-based hard carbon as well as preparation method and application thereof
CN116553521A
Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof
CN113381013A
Hard carbon, preparation method thereof and secondary battery
CN117486200A